Answer:
1-c
2-b
3-a
Step-by-step explanation:
1. 7y=14
y=2
-7y=-14
y=2
so the equation has one solution
2. 0=0
so the equation has infinite solution
3. 0=2 false
so the equation has no solution
We are given these three people age below:
- Jim's age
- Carla's age
- Tomy's age
We define the age of Jim as any variable, because the problem doesn't give any specific age. I will define Jim's age as x.
Next, Carla is 5 years older than Jim. That means if Carla is 5 years older, her age would be x+5.
Then Tomy is 6 years older than Carla. That means the age would be 6+(x+5).
The sum of their three ages is 31 years old. That means we add all these ages and equal to 31.
![\large{x + x + 5 + 6 + x + 5 = 31}](https://tex.z-dn.net/?f=%20%5Clarge%7Bx%20%2B%20x%20%2B%205%20%2B%206%20%2B%20x%20%2B%205%20%3D%2031%7D)
Combine like terms and solve for x.
![\large{3x + 16 = 31} \\ \large{3x = 31 - 16} \\ \large{3x = 15} \\ \large{x = 5}](https://tex.z-dn.net/?f=%20%5Clarge%7B3x%20%2B%2016%20%3D%2031%7D%20%20%5C%5C%20%20%5Clarge%7B3x%20%3D%2031%20-%2016%7D%20%5C%5C%20%20%5Clarge%7B3x%20%3D%2015%7D%20%5C%5C%20%20%5Clarge%7Bx%20%3D%205%7D)
Then we substitute the value of x in ages to find these three people ages.
- Jim's age = x = 5
- Carla's age = x+5 = 5+5 = 10
- Tomy's age = 6+(x+5) = 6+(5+5) = 6+10 = 16.
Answer
- Jim's age = 5
- Carla's age = 10
- Tomy's age = 16
Y = -2(x-5)^2 + 4
Note: vertex form is 0, f(x), y, or nothing= a(x-h)^2 + k
The opposite of the x value of the vertex is h
The y value value of the vertex is k.
Find a. Plug in (6,-10)
-10 = a(6-5)^2 + 4
-10 = 1a + 4
-10 = 5a
a = -2
Answer: 3.675 seconds
Step-by-step explanation:
Hi, when the object hits the ground, h=0:
h=−16t^2+48.6t+37.5
0=−16t^2+48.6t+37.5
We have to apply the quadratic formula:
For: ax2+ bx + c
x =[ -b ± √b²-4ac] /2a
Replacing with the values given:
a=-16 ; b=48.6; c=37.5
x =[ -(48.6) ± √(-48.6)²-4(-16)37.5] /2(-16)
x = [ -48.6 ± √ 4,761.96] /-32
x = [ -48.6 ± 69] /-32
Positive:
x = [ -48.6 + 69] /-32 = -0.6375
Negative:
x = [ -48.6 - 69] /-32 = 3.675 seconds (seconds can't be negative)
Feel free to ask for more if needed or if you did not understand something.
Answer:
see explanation
Step-by-step explanation:
Under a reflection in the y- axis
a point (x, y ) → (- x, y ) , then
J (1, 4 ) → J' (- 1, 4 )
K (1, 0 ) → K' (- 1, 0 )
L (4, 3 ) → L' (- 4, 3 )
Plot the points J', K', L' and connect them in order to obtain image